EU Financial Institutions: Experience and Crisis Challenge (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The article deals with the basic scientific and theoretical grounding made by national and foreign scholars in terms of economic institutionalism. The historicalexperience of formation and development of the institutional environment, that takes place in the process of the EU financial integration, is generalized. The history of the economic institutionalism theory was overviewed, the theoretical approaches to the interpretation of the terms «institute», «institution», «institutional environment» were revealed. The structure of the EU institutional environment was given. Factors, related to the national and international financial systems restructuring and state of the supranational currency and financial markets control, were systematized. The actions of the EU institutions during thefinancial crisis were revealed and their consequences in the process of reforms were analyzed
Keywords: EU, institute, institution, institutional environment, financial integration, globalization, financial crisis